Pragma-cognitive potential of paremia «Er tugan jerine, it toigan jerine» in Kazakh language - Kenzhalin Қ.К.; Abdirov Ө.Қ. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2022)
The article discusses the pragmatic potential of the paremia "Er tugan jerine, it toigan jerine.". The research work aims to identify the cognitive-pragmatic potential of the proverb at the present stage. The main idea of the research is to find answers to some problems of the philosophy of language, cognitive science and pragmalinguistics based on paremia. We see that thanks to the possibility of the anthropolinguistic paradigm, it is possible to freely integrate these fundamental areas. In addition to stable concepts such as theoretical conclusions and hypotheses, classifications related to the motivation of paroemias, the theory of mentalism, which is part of the object of the philosophy of language, is also considered in the framework of the research work. At the same time, the author tries to convey the vision of the theory of mentalism in the linguistic folklore, combined with cognitivism, through the categories of pragmalinguistics. Currently, the study of human behavior when labeling information in cognition is very relevant for science. The fact that this is related to the language of thought also increases the significance of the problem. In the course of the study, methods and techniques of ethnolinguistic, cognitive, and pragmatic study of linguistic and folklore unity were used. As a result, in recent years we have seen a decrease in the pragmatic and cognitive potential of the proverb cited. The author cites such factors as narrowing of cognition, volitional and mental incompetence as the reasons for the respondents’ misunderstanding of the proverb content. As a work devoted to the paremia in the pragmatic and cognitive aspect, the article will be important for those interested in these areas and researchers. The results and conclusions of the study can be used in pragmatic cognitive research, paremic dictionaries.